2022
DOI: 10.4103/jomfp.jomfp_110_21
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic activity of licorice extract in comparison with colchicine on areca nut-induced fibroblasts

Abstract: Objective: Oral submucous fibrosis (OSMF) is a debilitating chronic disease of the oral cavity with a high potential for malignant transformation. The main etiological agent attributed to the development of OSMF is the use of smokeless tobacco products like areca nut. There is no known cure for the disease. Current modalities of treatment do not provide a complete cure and often prove invasive for the patient. Herbal preparations using natural compounds and medicinal plant extracts have long since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Research has shown that glycyrrhiza and some of its extracts possess anti-PF effects ( Ghorashi et al, 2016 ). One of its saponin components, glycyrrhizic acid, has been found to inhibit the increase of TGF-β1, IL-17, and p-Smad2 expression in mice with PF, thus exerting anti-fibrotic effects by suppressing the expression of transforming growth factor and inflammatory factors ( Li et al, 2018 ; James et al, 2022 ). Another compound, licochalcone A, a phenolic chalcone derived from glycyrrhiza significantly inhibits TGF-β-induced transformation of fibroblast MRC-5 cells and reduces the expression of α-α-SMA and fibronectin (FN) in lung tissue.…”
Section: Pharmacological Study Of Mmdd In Pf Treatmentmentioning
confidence: 99%
“…Research has shown that glycyrrhiza and some of its extracts possess anti-PF effects ( Ghorashi et al, 2016 ). One of its saponin components, glycyrrhizic acid, has been found to inhibit the increase of TGF-β1, IL-17, and p-Smad2 expression in mice with PF, thus exerting anti-fibrotic effects by suppressing the expression of transforming growth factor and inflammatory factors ( Li et al, 2018 ; James et al, 2022 ). Another compound, licochalcone A, a phenolic chalcone derived from glycyrrhiza significantly inhibits TGF-β-induced transformation of fibroblast MRC-5 cells and reduces the expression of α-α-SMA and fibronectin (FN) in lung tissue.…”
Section: Pharmacological Study Of Mmdd In Pf Treatmentmentioning
confidence: 99%
“…Licorice was suggested as a treatment for OSF because it demonstrated antifibrotic effectiveness in human fibroblast cell lines [72].…”
Section: Oral Submucous Fibrosis (Osf)mentioning
confidence: 99%
“…Persimmon leaf (Diospyros kaki folium) extracts also demonstrate such ability with simultaneous activation of elastase [26]. Areca nut extracts cause disruption of the equilibrium between matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMP) [27].…”
Section: Herbal Preparations For Collagen Catabolism Regulationmentioning
confidence: 99%
“…Alkaloids from areca nut are the most important biologically for collagen metabolism regulation whilst tannin may have a synergistic role. These chemicals appear to interfere with the molecular processes of deposition and/or degradation of extracellular matrix molecules such as collagen [27,68].…”
Section: Herbal Pure Substances Effects On Collagenmentioning
confidence: 99%
See 1 more Smart Citation